Negative pole piece, preparation method thereof and electrochemical device

By using artificial graphite in the negative electrode sheet of lithium-ion battery and controlling its 3R phase content and Young's modulus gradient distribution, the problems of shedding and cycle performance degradation caused by high expansion rate of the negative electrode sheet are solved, and higher cycle performance and safety are achieved.

CN119725383APending Publication Date: 2025-03-28ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411963429.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The expansion rate of the negative electrode plate of the existing lithium-ion battery is large during charging and circulation, resulting in the problems of shedding of the electrode plate, degradation of circulation performance and safety and reliability.

Method used

The preparation method of the negative electrode sheet is adopted, wherein the negative electrode material includes artificial graphite, and the negative electrode active material layer is coated on the negative electrode current collector. By controlling the 3R phase content and Young's modulus gradient distribution of the artificial graphite, the expansion rate of the electrode sheet in the length and width directions is reduced.

Benefits of technology

It effectively reduces the volume expansion rate of the negative electrode sheet during the circulation process, reduces the possibility of the active material layer falling off, and improves the circulation performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725383A_ABST
    Figure CN119725383A_ABST
Patent Text Reader

Abstract

The invention provides a negative pole piece, a preparation method thereof and an electrochemical device, and particularly relates to the technical field of battery materials. The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is arranged on the negative electrode current collector and comprises a negative electrode material, and the negative electrode material comprises artificial graphite; wherein the expansion rate Sx of the negative pole piece in the length direction meets the condition that Sx is greater than or equal to 0.3 and less than or equal to 0.8%; and the expansion rate Sy of the negative pole piece in the width direction satisfies 0.2 < = Sy < = 0.5%. The negative pole piece disclosed by the invention has relatively small volume expansion, so that the possibility that the active material layer falls off in the circulating process can be reduced, the circulating performance is improved, and meanwhile, the quick charging time is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and particularly to a negative electrode sheet, a preparation method thereof, and an electrochemical device. Background Art

[0002] Lithium-ion batteries are widely used in various consumer electronic products, various electric vehicles, and wind and solar energy storage devices because of their high energy density, long cycle life, excellent mechanical properties, environmental friendliness, etc. The requirement for the energy density of the battery is getting higher and higher, and the specific capacity of the positive and negative electrode materials used is also required to be higher and higher; for example, graphite materials and silicon alloys with higher specific capacity will be used for the negative electrode; however, the high specific capacity negative electrode materials also bring larger swelling problems during charging and cycling, which will cause deformation, cycling degradation, and other safety and reliability problems to the battery cell.

[0003] Artificial graphite has good high-temperature performance and stable structure, but the long-cycle type of artificial graphite usually has the characteristics of low capacity and low compaction, and gradually does not meet the characteristics of high-energy-density long-cycle graphite in the current market. Moreover, on this basis, the cycle performance of lithium-ion batteries is largely affected by the negative electrode sheet of the lithium-ion battery. The swelling of the electrode sheet in the length and width directions during charging leads to serious detachment of the electrode sheet from the substrate, seriously affecting the safety and reliability of the battery cell. Summary of the Invention

[0004] In view of the above problems existing in the prior art, the present invention provides a negative electrode sheet, a preparation method thereof, and an electrochemical device to improve the problem of large swelling rate of the existing negative electrode sheet.

[0005] To achieve the above object and other related objects, the first aspect of the present invention provides a negative electrode sheet. The negative electrode material includes a negative electrode current collector and a negative electrode active material layer. The negative electrode active material layer is disposed on the negative electrode current collector. The negative electrode active material layer includes a negative electrode material, and the negative electrode material includes artificial graphite; wherein, the swelling rate Sx of the negative electrode sheet in the length direction satisfies 0.3 < Sx ≤ 0.8%; the swelling rate Sy of the negative electrode sheet in the width direction satisfies 0.2 < Sy ≤ 0.5%.

[0006] In an embodiment of the present invention, the Young's modulus of the negative electrode active material layer is 12 - 16 GPa.

[0007] In an embodiment of the present invention, the Young's modulus of the negative electrode active material layer is gradient-distributed from the middle region to both side edge regions in the width direction; wherein, in the width direction, the Young's modulus gradient ratio between the middle region and the edge region in the negative electrode active material layer is 1.02 - 1.13.

[0008] In one embodiment of the present invention, the artificial graphite includes a 3R phase, and the mass content of the 3R phase in the artificial graphite is 3% to 8%; the Young's modulus of the artificial graphite is 35 to 43 GPa.

[0009] A second aspect of the present invention provides a method for preparing a negative electrode sheet, comprising:

[0010] Providing a graphite raw material, and dividing the graphite raw material into a first graphite raw material and a second graphite raw material;

[0011] calcining the first graphite raw material to remove at least part of volatile components in the first graphite raw material;

[0012] The first graphite raw material and the second graphite raw material are arranged alternately in a furnace; the first graphite raw material and the second graphite raw material are graphitized to obtain artificial graphite;

[0013] The artificial graphite is used as a negative electrode material to prepare a coating, and the coating is coated on a negative electrode current collector to obtain a negative electrode sheet.

[0014] In one embodiment of the present invention, the volatile matter in the graphite raw material accounts for 10-15% of the total mass of the graphite raw material, the temperature of the calcination treatment is 1000-1400°C; the temperature of the graphitization treatment is 2300-2600°C.

[0015] In one embodiment of the present invention, before the first graphite raw material and the second graphite raw material are arranged in a furnace at intervals, the method further comprises:

[0016] The first graphite raw material is shaped so that the tap density of the first graphite raw material is greater than 0.95 g / cm 3 ; Performing spheroidization treatment on the first graphite raw material so that the sphericity of the first graphite raw material is greater than 0.9 and the roughness of the first graphite raw material is less than 5%;

[0017] The second graphite raw material is shaped so that the tap density of the second graphite raw material is greater than 0.9 g / cm 3 .

[0018] In one embodiment of the present invention, the preparation method further comprises compacting the first graphite raw material and the second graphite raw material before graphitization, the compaction pressure is 200 to 500 MPa, and the compaction time is 26 to 36 hours.

[0019] A third aspect of the present invention provides an electrochemical device, comprising the above-mentioned negative electrode plate, or a negative electrode plate prepared by the above-mentioned preparation method.

[0020] In one embodiment of the present invention, the electrochemical device comprises an electrolyte, and the mass content of propylene carbonate in the electrolyte is greater than or equal to 50%.

[0021] The present invention provides a negative electrode plate, wherein a negative electrode active material layer of the negative electrode plate is coated on a negative electrode current collector, the negative electrode active material layer comprises artificial graphite, and an expansion rate Sx of the negative electrode plate in the length direction satisfies 0.3≤Sx≤0.8%, and an expansion rate Sy in the width direction satisfies 0.2≤Sy≤0.5%. The smaller volume expansion rates of the negative electrode plate in the length direction and the width direction can reduce the possibility of the active material layer falling off during the cycle process, thereby improving the battery cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.

[0023] Figure 1 FIG. 1 is a schematic diagram of a process for preparing a negative electrode sheet according to an embodiment of the present invention. DETAILED DESCRIPTION

[0024] The following is an explanation of the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the features in the following embodiments and the embodiments can be combined with each other without conflict. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods for which specific conditions are not specified in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturers.

[0025] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.

[0026] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" and "one" etc. used in this specification are only for the convenience of description and are not intended to limit the scope of implementation of the present invention. Changes or adjustments to their relative relationships, without substantially changing the technical content, should also be regarded as the scope of implementation of the present invention.

[0027] In this specification, Dv50 may be defined as a particle size corresponding to 50% of the volume accumulation in the particle size distribution curve of the particles, Dv10 may be defined as a particle size corresponding to 10% of the volume accumulation in the particle size distribution curve of the particles, and Dv90 may be defined as a particle size corresponding to 90% of the volume accumulation in the particle size distribution curve of the particles. Dv10, Dv50, and Dv90 may be measured by, for example, a laser diffraction method. The laser diffraction method is generally capable of measuring particle sizes ranging from the submicron range to several millimeters, thereby obtaining highly reproducible and high-resolution results.

[0028] In this specification, Young's modulus refers to the degree of change in particle length per unit cross section after a powder is subjected to a certain tensile stress. Young's modulus E is defined as E = σ / ε, where σ represents the stress per unit area of ​​the material and ε represents the strain per unit length. The measurement method of Young's modulus refers to the GB / T 34186-2017 test.

[0029] Artificial graphite has good crystal phase regularity and can store more lithium ions, thus providing higher energy density. The regular crystal phase of artificial graphite is conducive to enhancing the cycle stability of the battery, improving battery performance, reducing side reactions, and improving battery safety. In addition, artificial graphite negative electrode materials can provide more active centers and fast lithium ion transmission channels for lithium ion intercalation, reduce polarization, and promote the diffusion of lithium ions, thereby improving fast charging performance. However, during the charging and discharging process, the artificial graphite negative electrode material will cause the volume expansion of the negative electrode sheet due to the change in lattice spacing. The volume expansion of the negative electrode sheet will not only increase the internal pressure of the battery, cause stress concentration inside the battery, and damage the structure of the battery, but also easily cause the negative active material layer on the negative electrode sheet to break, resulting in the loss of battery active materials and increased side reactions, resulting in a decrease in battery energy density and poor cycle performance. Therefore, controlling the expansion rate of the negative electrode sheet is of great significance for improving battery performance.

[0030] In order to reduce the impact of the expansion of the negative electrode plate on the battery performance, the first aspect of the present invention provides a negative electrode plate, which includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is arranged on at least one side of the negative electrode current collector along the thickness direction, the negative electrode active material layer includes a negative electrode material, and the negative electrode material includes artificial graphite; wherein the expansion rate Sx of the negative electrode plate in the length direction satisfies 0.3≤Sx≤0.8%; the expansion rate Sy of the negative electrode plate in the width direction satisfies 0.2≤Sy≤0.5%. The negative electrode plate in the present application has a smaller volume expansion, which can reduce the possibility of the active material layer falling off during the cycle process and improve the cycle life and storage life of the battery. wherein, the length direction of the negative electrode plate is the extension direction of the long side of the plate in the unfolded state, the width direction is the extension direction of the short side of the plate in the unfolded state, the length direction is perpendicular to the width direction, and the length direction and the width direction constitute the plane size of the plate. Taking the soft-pack battery assembled and wound into a bare cell as an example, the winding direction of the bare cell is the length direction of the negative electrode sheet, wherein an excess negative area (over hang) not covered by the negative active material layer is provided on the negative current collector of the negative electrode sheet, and the excess negative area is used to form a pole ear, and the side where the pole ear is located is the length side of the negative electrode sheet, and the side perpendicular to the length side is the width side.

[0031] In some embodiments, the Young's modulus of the negative electrode active material layer is any value in the range of 12 to 16 GPa, such as 12 GPa, 14 GPa or 16 GPa, etc. The negative electrode active material layer of the present application has greater mechanical rigidity, which can reduce the generation of micro defects during the cycle process, thereby improving the cycle life and electrochemical performance of the battery, reducing the increase in internal impedance, reducing safety hazards, improving the thermal stability of the battery, and reducing the consumption of electrolyte, thereby maintaining battery performance, extending the battery life, and reducing the risk of thermal runaway of the battery.

[0032] In some embodiments, the Young's modulus of the negative electrode active material layer is distributed in a gradient from the middle to both sides in the width direction, specifically, the Young's modulus of the middle region of the negative electrode active material layer in the width direction is higher than the Young's modulus of the edge regions on both sides; wherein, in the width direction of the negative electrode active material layer, the Young's modulus gradient ratio of the middle region to the edge region is any value in the range of 1.02 to 1.13, such as 1.02, 1.05, 1.1 or 1.13, etc. Exemplarily, the negative electrode active material layer is divided into three equal parts along the width direction, and from the edge on either side of the width direction of the negative electrode active material layer, 1 / 3 is the edge region, and from the middle position of the negative electrode sheet, from the middle position to 1 / 6 of the edges on both sides are the middle regions, that is, the negative electrode active material layer includes two edge regions and one middle region, and the middle region is located between the two edge regions. The Young's modulus of the middle region of the negative electrode active material layer is greater than that of the edge regions on both sides, which can reduce the squeezing of the middle region on both sides, reduce the local current density and alleviate the volume expansion, reduce the growth of dendrites and the generation of micro-defects, improve the cycle stability and electrochemical performance of the battery, and improve the battery safety. In addition, the gradient distribution of the Young's modulus also helps to optimize the electric field distribution and interface polarization, reduce the leakage current density, improve the energy density and efficiency, and enhance the mechanical properties of the solid electrolyte interface (Solid Electrolyte Interphase, SEI), better adapt to the volume change during the lithium ion deintercalation process, thereby reducing the damage of the SEI and improving the overall performance and life of the battery. Along the length direction of the negative electrode active material layer, the Young's modulus of the middle region and the Young's modulus of the edge region are uniformly distributed. The width direction of the negative electrode active material layer is consistent with the width direction of the negative electrode sheet, and the length direction of the negative electrode active material layer is consistent with the length direction of the negative electrode sheet.

[0033] In some embodiments, artificial graphite includes 3R phase (rhombus phase), the band structure of 3R phase graphite contains three-dimensional Dirac cone, the electronic state has a gap, and the electron transport is dominated by the surface state at low temperature, which has a positive effect on the electronic transport characteristics of the battery. The introduction of 3R phase in artificial graphite helps to improve the fast charging performance of the battery, reduce the voltage drop during fast charging, and increase the charging rate of the battery. The mass content of 3R phase in artificial graphite is any value between 3% and 8%, such as 3%, 5% or 8%, etc. The introduction of 3R phase in artificial graphite can increase the Young's modulus of artificial graphite, reduce the expansion rate of the negative electrode sheet, and help maintain the structural stability and cyclicity of the battery. However, excessive content of 3R phase will lead to an increase in the crystal phase defects of the graphite material, affecting the electrochemical performance of the battery. Therefore, the content of 3R phase is within the above-mentioned suitable range, which can not only reduce the expansion rate of the negative electrode sheet, improve the structural stability and cyclic stability of the battery, but also ensure that the battery has good electrochemical performance.

[0034] In some embodiments, the Young's modulus of the artificial graphite is any value between 35 and 43 GPa, such as 35 GPa, 40 GPa or 43 GPa, etc. When the Young's modulus of the artificial graphite is within the above-mentioned suitable range, it is possible to improve the Young's modulus of the negative electrode sheet and avoid excessive attenuation of the compaction density of the negative electrode sheet, thereby ensuring the energy density of the negative electrode sheet.

[0035] See also Figure 1 The second aspect of the present invention provides a method for preparing a negative electrode sheet, comprising the following steps:

[0036] S1. providing a graphite raw material, and dividing the graphite raw material into a first graphite raw material and a second graphite raw material;

[0037] S2, calcining the first graphite raw material to remove at least part of the volatile components in the first graphite raw material;

[0038] S3, arranging the first graphite raw material and the second graphite raw material in a furnace at intervals; performing graphitization treatment on the first graphite raw material and the second graphite raw material to obtain artificial graphite;

[0039] S4. Using artificial graphite as the negative electrode material to prepare a coating, coating the coating on the negative electrode current collector to obtain a negative electrode sheet.

[0040] In some embodiments, in step S1, the graphite raw material selects a material with volatile matter, for example, the graphite raw material selects coal-based needle coke mosaic coke, coal tar pitch, and resin pitch. Exemplarily, the graphite raw material selects coal-based needle coke, which has a higher capacity and a higher volatile content. In the present application, the volatile matter accounts for 10 to 15% of the total mass of the graphite raw material, for example, 10%, 12%, 13% or 15%. The content of the first graphite raw material and the second graphite raw material may be equal or unequal. In this embodiment, the content of the first graphite raw material and the second graphite raw material is equal.

[0041] In some embodiments, in step S2, calcining the first graphite raw material includes placing the first graphite raw material in a calcining furnace, raising the temperature of the calcining furnace to 1000-1400°C for calcining, and the calcining time is 3-5 hours. For example, the calcining temperature can be 1000°C, 1100°C, 1200°C, 1300°C or 1400°C, and the calcining time can be 3h, 4h or 5h. Too high a calcination temperature will result in excessive volatiles in the first graphite raw material. In the present application, part of the volatiles of the first graphite material can be removed by calcining, or all of the volatiles of the first graphite material can be removed. In this embodiment, all volatiles of the first graphite material are removed by calcining.

[0042] In some embodiments, in step S2, after calcining the first graphite raw material, the first graphite raw material and the second graphite raw material after the calcination are crushed separately, so that the particle size of the first graphite raw material and the second graphite raw material is controlled at 3 to 5 μm, and the particle size distribution (Dv90-Dv10) / Dv50 of the first graphite raw material and the second graphite raw material is controlled within 1.2.

[0043] In some embodiments, in step S3, before the first graphite raw material and the second graphite raw material are spaced apart in the furnace, the step further includes: shaping the first graphite raw material so that the tap density of the first graphite raw material is greater than 0.95 g / cm 3 ; The first graphite raw material is spheroidized so that the sphericity of the first graphite raw material is greater than 0.9 and the roughness of the first graphite raw material is less than 5%; the second graphite raw material is shaped so that the tap density of the second graphite raw material is greater than 0.9 g / cm 3 . Wherein, high-frequency heat shaping is adopted when shaping the first graphite raw material. Exemplarily, the frequency of high-frequency heat shaping is 80 Hz, and the shaping time is 1 to 3 hours, such as 1 hour, 2 hours or 3 hours. By shaping the first graphite raw material and the second graphite raw material separately and spheroidizing the first graphite raw material, the stress direction when the second graphite raw material squeezes the first graphite raw material during the subsequent graphitization process can be adjusted to better form the 3R phase in the first graphite raw material.

[0044] In some embodiments, step S3 specifically includes the following steps: dividing the cylindrical crucible furnace into a plurality of interval areas with a prefabricated grid plate, spacing the first graphite raw material and the second graphite raw material in the above-mentioned interval area, so that the first graphite raw material and the second graphite raw material are spaced and distributed on the same plane, and the furnace temperature is used to graphitize the first graphite raw material and the second graphite raw material, and the temperature of the graphitization treatment is 2300-2600°C, for example, 2300°C, 2400°C, 2500°C or 2600°C. This temperature is conducive to the crystal development of artificial graphite and has a great effect on improving the expansion rate of artificial graphite. During the graphitization process of the first graphite raw material and the second graphite raw material, since the volatile content in the second graphite raw material is higher than the volatile content in the first graphite raw material, the excess volatiles in the second graphite raw material diffuse outward, which will form air pressure on the first graphite raw material placed around, forcing the first graphite raw material to be squeezed during the graphitization sintering process, so that a 3R phase structure is formed in the first graphite raw material.

[0045] In some embodiments, in step S3, the preparation method further includes compacting the first graphite raw material and the second graphite raw material before graphitization. Specifically, the first graphite raw material and the second graphite raw material are arranged at intervals, and the first graphite raw material and the second graphite raw material are in the same horizontal plane, and the first graphite raw material and the second graphite raw material are compacted along the extension direction of the first graphite raw material and the second graphite raw material, and the pressure of the compaction treatment is 200-500MPa, such as 200MPa, 300MPa, 400MPa or 500MPa, etc., and the compaction treatment time is 24-36h, such as 24h, 28h, 30h, 32h or 36h. Compacting the first graphite raw material and the second graphite raw material can make the distribution of the first graphite raw material and the second graphite raw material more compact, so that during the graphitization process, the volatile matter of the second graphite raw material diffuses outward, and the first graphite raw material is squeezed more violently, which is conducive to the formation of the 3R phase in the first graphite raw material.

[0046] In some embodiments, in step S3, after obtaining the artificial graphite, the artificial graphite is further subjected to shaping and subdivision processing to control the Dv50 of the artificial graphite to any value between 8.5 and 11 μm, such as 8.5 μm, 10 μm, and 11 μm.

[0047] In step S4, when the coating is applied to the negative electrode current collector, the coating direction of the coating is the length direction of the negative electrode current collector, and after coating, the coating flows along the width direction of the negative electrode current collector. Exemplarily, the slurry is applied to the middle area of ​​the negative electrode current collector along the length direction of the negative electrode current collector, and the coating flows from the middle area to the edge areas on both sides along the width direction of the negative electrode current collector. During the flow process, the coating in the edge area dries faster due to the edge effect. After the coating dries, a negative electrode active material with a gradient distribution of Young's modulus is formed on the negative electrode current collector. The width direction of the negative electrode current collector is consistent with the width direction of the negative electrode pole piece, and the length direction of the negative electrode current collector is consistent with the length direction of the negative electrode pole piece. A third aspect of the present invention provides an electrochemical device, which includes the above-mentioned negative electrode pole piece or the negative electrode pole piece prepared by the above-mentioned preparation method.

[0048] In some embodiments, the electrochemical device may be a lithium ion primary battery, a lithium ion secondary battery, or the like. The structure of a lithium ion secondary battery is described in detail below, taking a lithium ion secondary battery as an example: a lithium ion secondary battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator, wherein the negative electrode sheet is the negative electrode sheet described above in the present invention or is prepared by the above-mentioned preparation method, and will not be described in detail here.

[0049] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on at least one side of the surface of the positive current collector. The positive current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam, etc. Among them, the thickness of the positive current collector is, for example, 8μm to 15μm. In the present embodiment, the positive current collector is, for example, aluminum foil, and the thickness of the aluminum foil is, for example, 13μm. The positive current collector has two oppositely disposed surfaces along its own thickness direction, and the positive active material layer can be disposed on the surface of any one side thereof, or on both surfaces. The positive active material layer includes a positive active material, a conductive agent and a binder. There is no specific restriction on the positive active material, the conductive agent and the binder here, and those skilled in the art can choose according to actual needs.

[0050] As an example, the positive electrode active material is selected from one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate, but the present application is not limited to these materials. The binder is selected from polyvinylidene fluoride (PVDF), polyethylene oxide (PEO), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR). The conductive agent is selected from one or at least two of conductive carbon black (Super P), acetylene black, graphene, carbon nanotubes, carbon nanofibers, etc. The ratio of the positive electrode active material, the conductive agent and the binder in the positive electrode active material layer can be set according to conventional methods in the art.

[0051] The electrolyte transfers lithium ions between the positive and negative electrodes, and the electrolyte can be selected from conventional combinations in the art. The electrolyte includes an organic solvent and a lithium salt, wherein the organic solvent can be selected from one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), etc., or a plurality of them mixed in any proportion. The lithium salt is selected from LiPF6 (Lithium hexafluorophosphate), LiBF 4 (Lithium Tetrafluoroborate)LiClO 4 (Lithium Perchlorate), LiAsF 6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl imide), LiTFSI (lithium bis(trifluoromethanesulfonyl imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO 2 F 2 (lithium difluorophosphate), LiDFOP (lithium difluorobisoxalate phosphate), LiTFOP (lithium tetrafluorooxalate phosphate) or a combination of multiple thereof in any proportion.

[0052] Propylene carbonate-based electrolytes can significantly inhibit lithium deposition during low-temperature charging, improve the low-temperature performance of the battery, and propylene carbonate-based electrolytes can also improve the fast-charging cycle performance of the battery. However, for conventional negative electrode materials, when the propylene carbonate content increases, propylene carbonate is easily co-embedded with solvated lithium ions on the surface of the graphite negative electrode, causing the graphite layer to peel off, and the reversible capacity of the graphite electrode decreases. The negative electrode plate prepared in the present invention, the mass content of propylene carbonate in the electrolyte is greater than or equal to 50%, which can not only improve the fast-charging performance of the battery, but also avoid the peeling of the artificial graphite layer.

[0053] In other embodiments, some film-forming additives and functional additives that can improve battery performance may be added to the electrolyte, such as vinylene carbonate (VC), 1,3-propane sultone (PS), diethylene sulfate (DTD), etc. Those skilled in the art may select according to actual needs.

[0054] The preparation process of lithium-ion secondary batteries is described below:

[0055] (1) Preparation of positive electrode sheet

[0056] The positive electrode active material lithium nickel cobalt manganese oxide (LiNi 0.6 Mn 0.2 Co 0.2 O 2 , NCM622), conductive agent SP, and binder PVDF are mixed in a mass ratio of 97:1.8:1.2 (a total of 100 mass parts), and 82 mass parts of NMP are added to obtain a positive electrode slurry; the obtained positive electrode slurry is coated on the surface of an aluminum foil, dried, rolled and compacted, and cut to obtain a positive electrode sheet.

[0057] (2) Preparation of negative electrode sheet

[0058] After mixing the negative electrode material, negative electrode conductive agent, negative electrode binder and thickener in a mass ratio of (90 to 99): (0.5 to 10): (1 to 3): (0.5 to 3), deionized water is added, and the mixture is fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both sides of the negative electrode current collector copper foil; after drying at room temperature, it is transferred to an oven for drying, and then cold pressed, cut and other processes are performed to obtain a negative electrode sheet. Among them, the negative electrode conductive agent can be selected from at least one of conductive materials such as carbon black (SuperP), acetylene black, carbon nanotubes (CNT), graphene, nano carbon fiber (VGCF). The negative electrode binder is selected from at least one of binding materials such as polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), etc. For example, the negative electrode binder is PAA and SBR, and the mass ratio of PAA to SBR is 1.3:0.5. The thickener is selected from carboxymethyl cellulose, which may be sodium carboxymethyl cellulose (CMC-Na) or lithium carboxymethyl cellulose (CMC-Li).

[0059] (3) Preparation of electrolyte

[0060] The electrolyte in this application can be selected from conventional electrolytes in the art, such as commercial electrolyte (manufacturer: Xinya Shanshan New Materials Technology (Quzhou) Co., Ltd., model: E3)

[0061] (4) Preparation of diaphragm

[0062] The diaphragm is arranged between the positive electrode and the negative electrode to play an isolating role. The diaphragm can be, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film, a polyethylene film or a composite film. The thickness of the diaphragm is 9 to 18 μm, the air permeability is 180 s / 100 mL to 380 s / 100 mL, and the porosity is 30% to 50%.

[0063] (5) Battery assembly:

[0064] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked or wound in sequence to form a bare battery cell; then wrapped with aluminum plastic film, transferred to a vacuum drying oven and dried at 120°C, sealed after injecting electrolyte, and the electrolyte is formed to finally prepare a soft-pack battery (i.e., a lithium-ion battery).

[0065] Those skilled in the art will understand that the above-described method for preparing a lithium-ion secondary battery is only an example, and other commonly used methods in the art may be used without departing from the contents disclosed in the present application.

[0066] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0067] Example 1

[0068] The preparation process of the negative electrode sheet in this embodiment is as follows:

[0069] (1) providing a graphite raw material with a volatile content of 13%, wherein the graphite raw material is selected from coal-based needle coke, and the graphite raw material is equally divided into a first graphite raw material and a second graphite raw material;

[0070] (2) calcining the first graphite raw material at 1250° C. for 4 hours to remove volatiles in the first graphite raw material, crushing the calcined first graphite raw material and the second graphite raw material to a particle size of 3 to 5 μm, and controlling the particle size distribution (Dv90-Dv10) / Dv50 of the first graphite raw material and the second graphite raw material to be within 1.2, and further, shaping the first graphite raw material so that the tap density of the first graphite raw material is greater than 0.95 g / cm 3 ; The first graphite raw material is spheroidized so that the sphericity of the first graphite raw material is greater than 0.9 and the roughness of the first graphite raw material is less than 5%; the second graphite raw material is shaped so that the tap density of the second graphite raw material is greater than 0.9 g / cm 3 .

[0071] (3) Arranging the first graphite raw material and the second graphite raw material in a furnace at intervals and keeping the first graphite raw material and the second graphite raw material on the same horizontal plane, compacting the first graphite raw material and the second graphite raw material at 300 MPa for 24 hours, graphitizing the first graphite raw material and the second graphite raw material at 2500° C. to obtain artificial graphite, and performing shaping and de-segmentation treatment on the obtained artificial graphite.

[0072] (4) Artificial graphite, conductive agent SP and binder (PAA and SBR, the mass ratio of the two is 1.3:0.5) and thickener carboxymethyl cellulose (CMC) are mixed in a mass ratio of 97.2:0.5:1.8:0.5 (a total of 100 parts by mass), and 82 parts by mass of deionized water are added and mixed evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on a copper foil, and after drying, rolling, cutting and other processes, a negative electrode sheet is prepared.

[0073] Example 2

[0074] The difference between this embodiment and embodiment 1 is that the volatile content in the graphite raw material is 15%, and the other steps are the same.

[0075] Example 3

[0076] The difference between this embodiment and embodiment 1 is that the volatile content in the graphite raw material is 10%, and the other steps are the same.

[0077] Example 4

[0078] The difference between this embodiment and embodiment 1 is that in step (3), the temperature for graphitizing the first graphite raw material and the second graphite raw material is 2300° C., and the remaining steps are the same.

[0079] Example 5

[0080] The difference between this embodiment and embodiment 1 is that in step (3), the temperature for graphitizing the first graphite raw material and the second graphite raw material is 2700° C., and the remaining steps are the same.

[0081] Example 6

[0082] The difference between this embodiment and embodiment 1 is that in step (2), the temperature for calcining the first graphite raw material is 1000° C., and the remaining steps are the same.

[0083] Example 7

[0084] The difference between this embodiment and embodiment 1 is that in step (2), the temperature for calcining the first graphite raw material is 1400° C., and the remaining steps are the same.

[0085] Comparative Example 1

[0086] This comparative example 1 provides a negative electrode sheet with the same component content as that of Example 1. The difference between this comparative example and Example 1 is that commercially available artificial graphite with a median particle size Dv50 of 12 μm is used as the negative electrode material.

[0087] To further verify the efficacy of the present invention, the performance parameters of the negative electrode materials and negative electrode sheets prepared in Examples 1 to 7 and Comparative Example 1 were first tested. The test results are shown in Table 1. The test process is as follows:

[0088] Young's modulus test of negative electrode material: please refer to GB / T 34186-2017 test;

[0089] 3R phase content test of negative electrode material: X-ray diffraction (XRD) test was performed on artificial graphite. The calculation formula of 3R phase content in artificial graphite is as follows:

[0090]

[0091] Among them,

[101] 3R is the diffraction intensity of the 3R phase in artificial graphite,

[101] 2H is the diffraction intensity of 2H (hexagonal phase) in artificial graphite, 15 / 12 is the K value of 3R phase;

[0092] Young's modulus test of negative electrode active material layer: Cut the negative electrode sheet according to its distribution, and test the Young's modulus value after cutting respectively. The calculation formula is E=σ / ε, where E represents Young's modulus, σ represents the stress per unit area of ​​the material, and ε represents the strain per unit length. In this application, the Young's modulus of the negative electrode active material layer is tested by nanoindentation method, and the specific test method is as follows: Use a diamond needle tip to press a nano-scale or micron-scale indentation on the surface of the negative electrode active material layer with extremely small force, and test the relationship between the pressure and the depth of the needle tip during loading and unloading. Since the depth of the indentation is much smaller than the thickness of the negative electrode active material layer, the active material layer on the surface of the negative electrode sheet can be directly tested when testing the Young's modulus of the negative electrode active material layer, and other components of the negative electrode sheet will not affect the test results.

[0093] Then, the negative electrode sheets prepared in Examples 1 to 7 and Comparative Example 1 were assembled into button-type half-cells, and the cells assembled in each example were tested. The test results are shown in Table 2.

[0094] The button half-cell is assembled as follows: lithium metal is used as the positive electrode, a polyethylene film is used as the diaphragm, the thickness of the diaphragm is 11 μm, the air permeability of the diaphragm is 230 s / 100 mL, and the porosity of the diaphragm is 40%; a commercial electrolyte is used as the electrolyte (the manufacturer is Xinya Shanshan New Materials Technology (Quzhou) Co., Ltd., model E3); 35 μL of electrolyte is dripped on each side of the diaphragm, and the positive electrode shell, positive electrode sheet, diaphragm, negative electrode sheet and negative electrode shell are assembled in sequence in a glove box (CR 2032 type), and placed at room temperature for 24 hours to allow the electrolyte to fully infiltrate the electrode sheet before subsequent battery testing.

[0095] The performance test of button half-cell is as follows:

[0096] Fast charging time: the battery cell is directly charged to 8% SOC with a current of 0.33C, and then the charging windows of 10%, 20%, 30%, 40%, 50%, 60%, 70% and 80% are tested according to the actual measured three-electrode window of the battery cell, which are C1, C2, C3, C4, C5, C6, C7 and C8 respectively. The battery cell is charged gradually to 80%, that is, C1 is used for 8%-10%, C2 is used for 10% to 20%, and so on. The charging time from 8% to 80% SOC is recorded as the measure of fast charging capability. The calculation formula is T = (0.02 / C1+0.1 / C2+0.1 / C3+0.1 / C4+0.1 / C5+0.1 / C6+0.1 / C7+0.1 / C8)×60.

[0097] Number of 2C cycles at room temperature: At 25°C, first charge and discharge the activated battery for one cycle at 0.1C in the charge and discharge voltage range of 2.8 to 4.5V, connect the activated lithium-ion battery prepared above to the Blue Electric charge and discharge tester, and then cycle it for a long time at a 2C rate until the ratio of the capacity of the nth cycle to the capacity of the first cycle of 2C is less than 80%, and the capacity retention rate of the n-1th cycle is defined as 80%, the number of cycles is recorded as n-1, and the test is stopped.

[0098] Storage days: At 25°C, use 0.33C current to set the capacity as C0, then store the battery at 60°C high temperature. After that, take out the battery every 7 days and test the capacity at room temperature as C1, C2…Cn. The number of days corresponding to the time when Cn is less than or equal to 80% of C0 for the first time is defined as the storage time.

[0099] Expansion rate: Take the side where the pole ear is located as the length side, and the side perpendicular to the length side as the width side. Use a micrometer to measure the length and width of the pole piece when fully charged and disassembled and the pole piece when fully discharged, Sx = (full charge length - full discharge length) / full discharge length × 100%, Sy = (full charge width - full discharge width) / full discharge width × 100%.

[0100] Table 1 Parameters of artificial graphite in Examples 1 to 7

[0101]

[0102] Table 2 Parameters of artificial graphite and negative electrode sheet in Examples 1 to 7 and Comparative Example 1

[0103]

[0104] Table 3 Test results of batteries assembled from Examples 1 to 7 and Comparative Example 1

[0105]

[0106] Compared with Comparative Example 1, Examples 1 to 7 improve the volume expansion problem of the negative electrode sheet during charging and discharging by reducing the expansion rate of the negative electrode sheet, reduce the shedding of the negative electrode sheet due to volume expansion, and improve the cycle performance of the battery.

[0107] By forming an appropriate content of 3R phase structure in artificial graphite, the Young's modulus of artificial graphite can be effectively improved, thereby reducing the expansion rate of the negative electrode plate. At the same time, it can also improve the conductivity of the negative electrode plate and improve the fast charging performance of the battery.

[0108] In summary, the present invention provides a negative electrode sheet and a preparation method thereof. The artificial graphite in the active material layer of the negative electrode sheet is obtained by graphitizing a graphite raw material having volatile components, and removing a portion of the volatile components in the graphite raw material before graphitization so that a 3R phase is generated during the graphitization process. The negative electrode sheet made using the artificial graphite has a small expansion rate in both its length and width directions, which can reduce the possibility of the active material layer falling off during the cycle and improve the cycle performance. Therefore, the present invention effectively overcomes some practical problems in the prior art and has a high utilization value and use significance.

[0109] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A negative electrode plate, characterized in that: include: Anode current collector; A negative electrode active material layer, which is disposed on the negative electrode current collector, the negative electrode active material layer comprises a negative electrode material, and the negative electrode material comprises artificial graphite; The expansion rate Sx of the negative electrode sheet in the length direction satisfies 0.3≤Sx≤0.8%; the expansion rate Sy of the negative electrode sheet in the width direction satisfies 0.2≤Sy≤0.5%.

2. The negative electrode sheet according to claim 1, characterized in that: The Young's modulus of the negative electrode active material layer is 12 to 16 GPa.

3. The negative electrode sheet according to claim 1, characterized in that: The Young's modulus of the negative electrode active material layer is distributed in a gradient from the middle region to the edge regions on both sides in the width direction; wherein, in the width direction, the Young's modulus gradient ratio between the middle region and the edge region in the negative electrode active material layer is 1.02 to 1.

13.

4. The negative electrode sheet according to claim 1, characterized in that: The artificial graphite includes a 3R phase, and the mass content of the 3R phase in the artificial graphite is 3% to 8%; the Young's modulus of the artificial graphite is 35 to 43 Gpa.

5. A method for preparing a negative electrode sheet according to any one of claims 1 to 4, characterized in that: include: Providing a graphite raw material, and dividing the graphite raw material into a first graphite raw material and a second graphite raw material; calcining the first graphite raw material to remove at least part of volatile components in the first graphite raw material; The first graphite raw material and the second graphite raw material are arranged alternately in a furnace; the first graphite raw material and the second graphite raw material are graphitized to obtain artificial graphite; The artificial graphite is used as a negative electrode material to prepare a coating, and the coating is coated on a negative electrode current collector to obtain a negative electrode sheet.

6. The preparation method according to claim 5, characterized in that: The volatile matter in the graphite raw material accounts for 10-15% of the total mass of the graphite raw material. The temperature of the calcination treatment is 1000-1400°C; the temperature of the graphitization treatment is 2300-2600°C.

7. The preparation method according to claim 5, characterized in that: Before the first graphite raw material and the second graphite raw material are arranged in a furnace at intervals, the method further comprises: The first graphite raw material is shaped so that the tap density of the first graphite raw material is greater than 0.95 g / cm 3 ; Performing spheroidization treatment on the first graphite raw material so that the sphericity of the first graphite raw material is greater than 0.9 and the roughness of the first graphite raw material is less than 5%; The second graphite raw material is shaped so that the tap density of the second graphite raw material is greater than 0.9 g / cm 3 .

8. The preparation method according to claim 5, characterized in that: The preparation method further comprises compacting the first graphite raw material and the second graphite raw material before graphitization, wherein the compacting pressure is 200 to 500 MPa and the compacting time is 26 to 36 hours.

9. An electrochemical device, characterized in that: It comprises the negative electrode sheet as described in any one of claims 1 to 4, or the negative electrode sheet prepared by the preparation method as described in any one of claims 5 to 8.

10. The electrochemical device according to claim 9, characterized in that The electrochemical device comprises an electrolyte, and the mass content of propylene carbonate in the electrolyte is greater than or equal to 50%.